ANALYZING AND EVALUATING THE INFORMATION TECHNOLOGY SYSTEM IN PT. REPEX PERDANA INTERNATIONALS LOGISTIC ACTIVITIES - Rauf, Zulfahmi Azis (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
Innovations are one of the most important jobs that are conducted byalmost all organizations, business and firms in order to improve their currentoperation capabilities. In this research, the chosen company, Repex PerdanaInternational (RPI) the license owner of FedEx International, innovate a newinformation technology into their system in order to improve their performance in thelogistics. The goal of this research is to âanalyzing and evaluating the recentimplementation of Information Technology (IT) system in RPI, specify in itseffectiveness and efficiencyâ. The purpose of analyzing the IT system is to see whatkind of improvement that achieved so far and at the end devise a possiblerecommendation and suggestion to improve it. As the research undertaken, someconclusions have been made on the basis of research findings which are showingpositive results of the investment. However some drawbacks also founded from thesystem and in the end there will be recommendations to counter these drawbacks,future improvement, as well as future research.